A comprehensive computational design for microstrip passive and active linear circuits - EI-Sayed A. EI-Badawy; Said H. Ibrahim (2001)
This paper presents a user-oriented comprehensive computational program for designing linear active and passive microstrip circuits such as amplifiers, oscillators,mixers. lowpass filters and cuoplers. The substrate parameters and the characteristic impedance of the microstrip lines are given to the program as a common statement. Examples for the design of a 3 GHz high gain amplifier; 2.6-GHz oscillators, ring coupler operated at 3 GHz, and maximally-flat lowpass filter operated at 2 GHz with 0.75 GHz cutoff frequency are conducted. The introduced program is compared to other available ones